2018
DOI: 10.20473/j.djmkg.v51.i3.p133-137
|View full text |Cite
|
Sign up to set email alerts
|

Cytoxicity test of NaOCl and Mangosteen (Garcinia Mangostin L.) peel extract used as an irrigation solution in human periodontal ligament fibroblast cells (HPdLFc)

Abstract: Background: Root canal irrigation is an important stage in root canal treatment as it is requires to eliminate necrotic and debris tissue as well as root canal wetting. Unfortunately, root canal irrigation can cause the material utilised to pass into the apical foramen leading to periapical complications. Consequently, the irrigation solution should have low toxicity. Sodium hypochlorite (NaOCl) is a commonly used irrigation solution since it has antibacterial properties. Moreover, NaOCl is also known to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Bacterial elimination from the root canal holds the key to a successful endodontic treatment. 9,10 The primary factor to achieve this and to prevent future intrusion of bacteria is a thorough and meticulous technique. When these factors are taken into account, success rate has been shown to be as high as 94%.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial elimination from the root canal holds the key to a successful endodontic treatment. 9,10 The primary factor to achieve this and to prevent future intrusion of bacteria is a thorough and meticulous technique. When these factors are taken into account, success rate has been shown to be as high as 94%.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Mangosteen rind consists of active chemical ingredients such as xanthone, flavonoid, saponin, tannin, phenol, gartanine, garcinon, vitamins B1, B2, terpenes, anthocyanins, and other biologically active substances that support its medicinal properties. 14 The significant bioactive secondary metabolites of mangosteen are xanthones derivatives (i.e., α- and γ-mangosteen have antioxidant, antiproliferative, antibacterial, and anti-inflammatory effects). 15 , 16 Xanthone substances have considerable ability to regulate and minimize oxidative damage by hampering or preventing oxidation caused by reactive oxygen species, thus inhibiting the degeneration of cells.…”
Section: Introductionmentioning
confidence: 99%
“…2 Fibroblast cells are the main cells in the periodontal ligament, so the irrigation solution that comes out of the apical foramen will cause a cytotoxic effect on fibroblast cells and complications in the periapical tissue. 3,4 The cytotoxic effects of irrigants can cause periapical tissue degeneration and delayed wound healing due to irritation and tissue damage. 3 Research conducted by Karkehabadi on the cytotoxicity test of NaOCl irrigating solution on human periodontal ligament fibroblast cells (HPdLFc) found that NaOCl was toxic at a concentration of 0.025%, while at a concentration of 0.4% it caused the death of all cells.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The cytotoxic effects of irrigants can cause periapical tissue degeneration and delayed wound healing due to irritation and tissue damage. 3 Research conducted by Karkehabadi on the cytotoxicity test of NaOCl irrigating solution on human periodontal ligament fibroblast cells (HPdLFc) found that NaOCl was toxic at a concentration of 0.025%, while at a concentration of 0.4% it caused the death of all cells. 5 The entry of NaOCl into the periapical tissue can occur because of the wide apical foramen, lack of apical constriction, and high pressure during root canal irrigation.…”
Section: Introductionmentioning
confidence: 99%